2019
DOI: 10.1101/682658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context-specific functions of Notch in Drosophila blood cell progenitors

Abstract: statement Notch signaling regulates differently distinct populations of blood cell progenitors of the Drosophila larval hematopoietic organ.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…3C’). This pattern of activity was reminiscent of the positioning of the intermediate or transitioning progenitors (Blanco-Obregon et al, 2020) and the sensor expression analysis highlighted dopamine signalling at this interface.…”
Section: Resultsmentioning
confidence: 81%
“…3C’). This pattern of activity was reminiscent of the positioning of the intermediate or transitioning progenitors (Blanco-Obregon et al, 2020) and the sensor expression analysis highlighted dopamine signalling at this interface.…”
Section: Resultsmentioning
confidence: 81%
“…Its usefulness is in that it provides a broad landscape for gene expression. However, in the case of the lymph gland, a finer analysis at a cellular level is warranted because of the considerable heterogeneity reported amongst the cells belonging to individual zones (Jung et al 2005; Kurucz et al 2007; Oyallon et al 2016; Baldeosingh et al 2018; Blanco-Obregon et al 2020). We therefore use single cell RNA-Seq to complement and enhance the bulk RNA-Seq data and to characterize subpopulations of cells that reside within each zone.…”
Section: Resultsmentioning
confidence: 99%
“…We took advantage of known differences in the expression patterns of two progenitor drivers (Tep4-GAL4 92,93 and dome MESO -GAL4 32,92,94,95 ) to better understand the spatial regulation of the cell cycle. While dome MESO -GAL4 is ubiquitously active in all progenitors, Tep4-GAL4 expression is confined to an inner subset of less mature dome MESO -expressing cells, which have been referred to as "core progenitors", located closer to the dorsal vessel and farther away from the edge of the lymph gland [36][37][38][39] . The distinction in the expression of these two drivers is best appreciated in live imaging of the larva (Figure 5M-O).…”
Section: Spatial Regulation Of the Cell Cyclementioning
confidence: 99%
“…Recent genetic [36][37][38][39] and transcriptomic studies 40,41 have identified considerable heterogeneity within the progenitor population. These subpopulations are spatially arranged so that the innermost ones ("core" progenitors), closest to the dorsal vessel, are the least mature, while the most mature ones ("distal" progenitors) are found at the periphery of the MZ near the site of differentiation.…”
Section: Introductionmentioning
confidence: 99%